2014
DOI: 10.1002/ejoc.201402469
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Substituted Biaryls through Gold‐Catalyzed Petasis–Ferrier Rearrangement of Propargyl Ethers

Abstract: A triphenylphosphine‐catalyzed cascade reaction of unsaturated pyrazolones with dialkyl acetylenedicarboxylates or but‐3‐yn‐2‐one to synthesize the bioactive pyrano[2,3‐c]pyrazoles in moderate to excellent yields has been developed. Meanwhile, spiro‐cyclopentanone‐pyrazolones were also first constructed by the triphenylphosphine‐catalyzed cascade reaction of unsaturated pyrazolones with 4‐phenylbut‐3‐yn‐2‐one in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The more significant change in the σCH* population (0.08 e ) relative to the σCH population (0.03 e ) suggests that the C−H bond is a net acceptor. Interestingly, the positively charged Au center, which is commonly used as a Lewis‐acidic catalyst in organic reactions [33,34,43–52] serves as a donor in this particular situation. Again, the Au‐complex is a better donor than its Ag and Cu counterparts (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…The more significant change in the σCH* population (0.08 e ) relative to the σCH population (0.03 e ) suggests that the C−H bond is a net acceptor. Interestingly, the positively charged Au center, which is commonly used as a Lewis‐acidic catalyst in organic reactions [33,34,43–52] serves as a donor in this particular situation. Again, the Au‐complex is a better donor than its Ag and Cu counterparts (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Such reactions were successfully used for the preparation of biologically active heterocycles. Subsequently, Pati and Alabugin reported that, when an aromatic ring can be used as an endocyclic donor with the assistance of a properly positioned exocyclic aryl donor, the Au-catalyzed PFR can be utilized for synthesis of carbocyclic aromatic systems (Scheme 26, bottom) [93].…”
Section: Petasis-ferrier Rearrangementmentioning
confidence: 99%
“…Overall, the mild and efficient Au-catalyzed Petasis-Ferrier/aromatization sequence converts alkynes into activated enol ethers. Alkoxy substitution in the products can be used for subsequent synthetic transformations, such as the highly regioselective oxidative dimerization into tetranaphthyls [93].…”
Section: Petasis-ferrier Rearrangementmentioning
confidence: 99%
“…Synthesis of highly substituted piperidines has been developed by the Rhee group, whereas Zhang et al reported carboalkoxylation with efficient chirality transfer from enantioenriched benzylic ethers and N,O-acetals. , Pd- and Pt-catalyzed cycloisomerizations of o -alkynyl­benzaldehyde acetals and thioacetals to functionalized indenes were described by Yamamoto . Recently, we reported Au-catalyzed cycloisomerization of aryl propargyl ethers that opened synthetic access to substituted biaryls with a functionalized naphthalene core . There have been several examples of Au-assisted formation of aromatic cores …”
mentioning
confidence: 99%
“…5i Recently, we reported Au-catalyzed cycloisomerization of aryl propargyl ethers that opened synthetic access to substituted biaryls with a functionalized naphthalene core. 6 There have been several examples of Au-assisted formation of aromatic cores. 7 In this work, we report the synthesis of fused catechol ethers via a room-temperature gold-catalyzed cycloisomerization reaction.…”
mentioning
confidence: 99%